Heterozygous NPR2 Mutation in Two Family Members with Short Stature and Skeletal Dysplasia - Marianne Jacob; Surabhi Menon; Christina Botti; Ian Marshall (Case Reports in Endocrinology)
Endochondral ossification at the level of the growth plate, an essential process involved in longitudinal growth, is regulated by hormonal and local factors including C-type natriuretic peptide and its receptor, natriuretic peptide receptor B. Biallelic loss-of-function mutations in the NPR2 gene, which encodes this receptor, cause acromesomelic dysplasia, Maroteaux type (AMDM), a skeletal dysplasia characterized by severe short stature and disproportionate shortening of limbs. Heterozygous NPR2 mutations have been reported in patients previously classified with idiopathic short stature (ISS). We report the presentation of a 7-year-old girl and her mother with short stature, both of whom were identified with the same NPR2 mutation, and who demonstrated clinical and radiological features consistent with a skeletal dysplasia. We also report the patient’s response to recombinant human growth hormone (rhGH) over a 2-year period. We encourage clinicians who evaluate children with ISS to consider genetic testing, particularly when the presentation is associated with features suggestive of a skeletal dysplasia.